DIFFUSION AND INSTITUTIONALIZATION OF INSTRUCTIONAL TECHNOLOGY AS AN EFFORT TO IMPROVE THE QUALITY OF LEARNING - Hasan Basri (Jurnal Penelitian Progresif, 2022)
The presence of technology has made it easier for humans to manage various aspects of life. Aspects of education, for example, technology has played an important role in the learning process. Recently, many educational institutions have adopted technology to facilitate the teaching and learning process both inside and outside the classroom, technology has even been used widely in distance learning systems. However, there are still many educational institutions that are not 'familiar' with instructional technology.